Cecal volvulus after robotic assisted laparoscopic hysterectomy in a gynecologic oncology patient: A case report - Divya Gowthaman; Lauren Scanlon; John C. McAuliffe; Shabnam Fidvi; Carly Schwartz; Sara S. Isani (Elsevier, 2024)
Cecal volvulus is a rare and life-threatening cause of intestinal obstruction with multiple risk factors including prior abdominal surgery and cecal hypermobility. Although its incidence has been reported after common procedures such as cholecystectomy and appendectomy, it has not been well studied after laparoscopy, especially in gynecological surgeries. If untreated, a cecal volvulus can result in serious complications such as intestinal strangulation, necrosis, or perforation. Therefore, early identification of risk factors and intervention is important in prevention of these sequelae. Here, we report a case of cecal volvulus in a patient with endometrial carcinoma after a staging robotic-assisted laparoscopic hysterectomy and the risk factors that may have led to her complication.